The lemon market of insolvency proceedings in Spain in the new normal: Information, asymmetry, and adverse selection problems - Unai Olabarrieta; Leire San-Jose; Andrés Araujo (Cogent Business & Management, 2023)
Insolvency proceedings are strategic for the competitiveness of a national economy. The new law, but also new financial situation of organizations affect the new normal of insolvency framework. In Europe, standards aimed at creating an efficient framework for corporate insolvency resolution are constantly changing to enhance the efficiency of such mechanisms. This pursuit contrasts with the lack of specific efficiency data available to both legislators and researchers, there are no solid statistics to investigate the phenomenon from the perspective of its efficiency, which makes it impossible in practice to investigate its explanatory variables. Previous studies have led us to reflect on key information asymmetry and adverse selection problems resulting from a gap between the new challenges on insolvencies processes and options, because the lack of information. Based on this reflection, we have identified parallelisms between the lemon market, and current insolvency proceedings in Spain. Although, the legal system is modified, the insolvency process itself is a drag, for the achievement of the long-awaited efficiency of the process. It will be necessary to change, not only the legislation, but also the information provided, and create a new insolvency system because actual has "lemons signals", this circumstance is producing negative effects on the efficiency and competence of a key figure in the process: the insolvency administrator.
Keywords: 650; adverse selection; bankruptcy; efficiency; information asymmetries; insolvency administrator; insolvency proceedings; lemon market; moral hazard